The Common Agricultural Policy and the EU budget: stasis or change? - Alan Greer (European Journal of Government and Economics (EJGE), 2013)
After highlighting the budgetary context and the historical trends on the funding of the CAP, this paper considers contemporary debates about its reform in the context of two 'historic firsts'. Negotiations about the multiannual financial framework (MFF) for 2014-20 for the first time took place in tandem with a proposed CAP reform, within the broader context set by the financial crisis after 2008. Second, the CAP reform debates took place within the new institutional arrangements introduced in the Lisbon Treaty, which by extending the co-decision mechanism to the CAP potentially has increased the influence of the European Parliament (EP). Indeed the CAP reform dossiers were the first real test of these new arrangements and provide an insight into how the new institutional structure will work in practice. In both cases the paper highlights a continuing cleavage among member states and stakeholder interests ~- that maps partly onto a broader budgetary gainers/losers division - between advocates of radical reform (e.g. the UK, Sweden) and those who favour the retention of the traditional CAP (such as France, Spain and Ireland).
Keywords: 330; Agricultural Policy; CAP reform; Multi-annual Financial Framework; co-decision